A chloroplast‐localized protein LESION AND LAMINA BENDING affects defence and growth responses in rice. Issue 4 (10th February 2016) - Tamiru, Muluneh; Takagi, Hiroki; Abe, Akira; Yokota, Takao; Kanzaki, Hiroyuki; Okamoto, Haruko; Saitoh, Hiromasa; Takahashi, Hideyuki; Fujisaki, Koki; Oikawa, Kaori; Uemura, Aiko; Natsume, Satoshi; et al.
Summary: Understanding how plants allocate their resources to growth or defence is of long‐term importance to the development of new and improved varieties of different crops. Using molecular genetics, plant physiology, hormone analysis and Next‐Generation Sequencing (NGS)‐based transcript profiling, we have isolated and characterized the rice ( Oryza sativa ) LESION AND LAMINA BENDING ( LLB ) gene that encodes a chloroplast‐targeted putative leucine carboxyl methyltransferase. Loss of LLB function results in reduced growth and yield, hypersensitive response (HR)‐like lesions, accumulation of the antimicrobial compounds momilactones and phytocassanes, and constitutive expression of pathogenesis‐related genes. Consistent with these defence‐associated responses, llb shows enhanced resistance to rice blast ( Magnaporthe oryzae ) and bacterial blight ( Xanthomonas oryzae pv. oryzae ). The lesion and resistance phenotypes are likely to be caused by the over‐accumulation of jasmonates (JAs) in the llb mutant including the JA precursor 12‐oxo‐phytodienoic acid. Additionally, llb shows an increased lamina inclination and enhanced early seedling growth due to elevated brassinosteroid (BR) synthesis and/or signalling. These findings show that LLB functions in the chloroplast to either directly or indirectly repress both JA‐ and BR‐mediated responses, revealing a possible mechanism for controlling how plants allocate resources for defence and growth.